Weighted norm inequalities and indices - Joaquim Martín; Mario Milman (Journal of Function Spaces and Applications)
We extend and simplify several classical results on weighted norm inequalities for classical operators acting on rearrangement invariant spaces using the theory of indices. As an application we obtain necessary and sufficient conditions for generalized Hardy type operators to be bounded on ?p(w), ?p,8(w), Gp(w) and Gp,8(w).